2018
DOI: 10.1371/journal.pone.0192584
|View full text |Cite
|
Sign up to set email alerts
|

Do singles or couples live healthier lifestyles? Trends in Queensland between 2005-2014

Abstract: ObjectivesTo compare the frequency of and trends in healthy lifestyle factors between singles and couples.MethodsCross-sectional data from annual surveys conducted from 2005–2014 were used. The pooled sample included 15,001 Australian adults (mean age: 52.9 years, 50% male, 74% couples) who participated in the annual Queensland Social Survey via computer-assisted telephone interviews. Relationship status was dichotomised into single and couple. Binary logistic regression was used to assess associations between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 37 publications
2
20
1
2
Order By: Relevance
“…In this study, divorced/separated/bereaved adults were more likely to be currently smoking and currently smoking/drinking monthly compared with married adults; this finding supports previous findings [41,42,43]. Harmful lifestyle habits, such as smoking or heavy alcohol drinking, may be more noticeable by spouses and may be changed through the support and encouragement of spouses, especially wives [41,42,44]. A spouse is the most influential person to a smoker or drinker as he/she is the person with whom the latter is in a romantic relationship; therefore, a couple-based intervention that helps adults quit smoking and prevent heavy alcohol drinking, may be more helpful in changing negative health behaviors, especially among men [43].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, divorced/separated/bereaved adults were more likely to be currently smoking and currently smoking/drinking monthly compared with married adults; this finding supports previous findings [41,42,43]. Harmful lifestyle habits, such as smoking or heavy alcohol drinking, may be more noticeable by spouses and may be changed through the support and encouragement of spouses, especially wives [41,42,44]. A spouse is the most influential person to a smoker or drinker as he/she is the person with whom the latter is in a romantic relationship; therefore, a couple-based intervention that helps adults quit smoking and prevent heavy alcohol drinking, may be more helpful in changing negative health behaviors, especially among men [43].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported that living alone is more likely associated with multiple lifestyle risk factors, such as smoking and heavy alcohol drinking [27,40,41,42,43], even when gender difference is considered [44]. In this study, divorced/separated/bereaved adults were more likely to be currently smoking and currently smoking/drinking monthly compared with married adults; this finding supports previous findings [41,42,43]. Harmful lifestyle habits, such as smoking or heavy alcohol drinking, may be more noticeable by spouses and may be changed through the support and encouragement of spouses, especially wives [41,42,44].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the non-Indigenous group, those living in families with children under 18 were at greatest risk of being overweight or obese. A recent Australian study showed that compared with singles, couples were significantly less likely to be within a normal weight range [45], while another associated lower levels of physical activity in the time of transition to parenthood as a main contributor to increased obesity of parents [46].…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study from the Netherlands confi rmed that older people as well as married people had a higher likelihood of quitting smoking, both for men and women (van Loon et al 2005). Schoeppe et al (2018) investigated with cross-sectional data the frequency of healthy lifestyle factors in 15,001 Australian singles (never married, widowed, divorced), and couples (married and unmarried). The authors identifi ed trends in these healthy lifestyle factors between 2005 and 2014.…”
Section: Partnership and Smokingmentioning
confidence: 99%